Perspektif Etika Bisnis Mahasiswa Terhadap Penggunaan Software Asli Dan Bajakan Di Kotamadya Pontianak - Wahyudi, Hijrah; Mardiyati, Mardiyati (Jurnal Ekonomi STIEP ( JES ), 2019)
The purpose of this research is to know the college student’s perspective of business ethic about genuine software fake software; to socialise and disseminate some freewaresto the college students. This analysis is done by using descriptive analysis in order to answer the research. This research is done to 100 college students ( 50 persons from STIE Indonesia Pontianak, and 50 persons from STIE Pontianak). Result of the research concludes that happened gap, in which the perspective of business ethic is above the piracy of the software. .